Fulfillment of Workers' Rights in The Terminating Employment Relationships During The Covid-19 Pandemic - Rita Rahmawati; Nurul Qomariyah; Trianah Shofiani (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
This paper analyzes the fulfillment of workers' rights in Termination of Employment Relationship during the Covid 19 Pandemic at PT Sukorintek and legal remedies that can be taken to fulfill workers' rights.This empirical juridical research uses a qualitative approach. Data collection techniques using interviews and documentation studies. The analysis technique uses an interactive model. The results showed that, Fulfilling workers' rights in Termination of Employment Relationship during the Covid 19 Pandemic at PT. Sukorintex Indah Textile is not in accordance with the provisions of the labor laws and regulations. PT. Sukorintex only provides severance pay to workers as much as 0.40 (40%) of the amount that should be received by workers. Whereas according to the labor laws and regulations, workers who are laid off due to force majeure which do not cause the company to close as in the case of PT Sukorintek are entitled to severance pay of 0.75 (zero point seventy five) times of service; 1 (one) time service award in accordance with the period of service and compensation for other entitlements in accordance with the period of service. Legal remedies that can be taken in the case of PT. Sukorintex, among others: using non-litigation, namely bipartite negotiations, mediation, and conciliation or using litigation, namely through the Industrial Relations Court at the District Court in the legal area where the worker/laborer works.